Zebularine protects against blood-brain-barrier (BBB) disruption through increasing the expression of zona occludens-1 (ZO-1) and vascular endothelial (VE)-cadherin. Issue 2 (1st February 2022) - Zeng, Xiangliang; He, Guohua; Yang, Xirong; Xu, Guoyao; Tang, Yidan; Li, Hanwen; Yu, Bing; Wang, Zhen; Xu, Wei; Song, Kangping
ABSTRACT: Blood-brain-barrier (BBB) disruption is an important pathological characteristic of ischemic stroke (IS) and mainly results from dysfunction of brain vascular endothelial cells and tight junctions. Zebularine is a novel inhibitor of DNA methyltransferase (DNMT). Here, we assessed its effects on BBB disruption in IS. Firstly, we reported that Zebularine maintained BBB integrity in middle cerebral artery occlusion (MCAO) mice by increasing the expressions of zona occludens-1 (ZO-1) and vascular endothelial (VE)-cadherin. Importantly, we found that Zebularine reduced the production of pro-inflammatory cytokines, attenuated brain edema, and improved neurological deficits. In in vitro experiments, the bEnd.3 brain endothelial cells were exposed to oxygen and glucose deprivation/reoxygenation (OGD/R), and the protective effects of Zebularine were assessed. Our findings demonstrated that Zebularine prevented OGD/R-induced cytotoxicity by reducing the release of lactate dehydrogenase (LDH). Additionally, Zebularine protected bEnd.3 cells against OGD/R-induced hyper-permeability and reduction of trans-endothelial electrical resistance (TEER). Notably, we found that treatment with Zebularine activated the Adenosine 5ʹ-monophosphate (AMP)-activated protein kinase (AMPK) pathway by increasing the phosphorylation of adenosine monophosphate-activated protein kinase α (AMPKα). Blockage of AMPKα using its specific inhibitor compound C abolished the beneficial effects of Zebularine in mitigating endothelial hyper-permeability by reducing the expressions of ZO-1 and VE-cadherin. These findings suggest that the protective effects of Zebularine against OGD/R-induced endothelial hyper-permeability are mediated by the activation of AMPKα. In conclusion, our study sheds light on the potential application of Zebularine in the treatment of IS. Graphical abstract: uf0001